2021
DOI: 10.1029/2020ja029099
|View full text |Cite
|
Sign up to set email alerts
|

Automated Identification of Current Sheets—A New Tool to Study Turbulence and Intermittency in the Solar Wind

Abstract: We propose a new method of the automated identification of current sheets (CSs) that represents a formalization of the visual inspection approach employed in case studies. CSs are often identified by eye via the analysis of characteristic changes in the interplanetary magnetic field (IMF) and plasma parameters. Known visual and semi‐automated empirical methods of CS identification are exact but do not allow a comprehensive statistical analysis of CS properties. Existing automated methods partially solve this p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 112 publications
0
16
0
Order By: Relevance
“…On the other hand, this limits their validity to scales much larger than the electron scales. Space observations of collisionless plasma turbulence by multi-spacecraft missions (Cluster and MMS) in the Earth's magnetosphere and the solar wind, however, revealed electron-and ion-scale breaks in the power spectra as well as the formation of current sheet (CS) structures from ion to electron scales [20][21][22] . On the other hand, even hybrid-kinetic simulations with inertia-less electrons have already shown that in evolving turbulent CSs, the electrons become the main current carriers 15 and that these CSs thin down to the grid scale 23 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this limits their validity to scales much larger than the electron scales. Space observations of collisionless plasma turbulence by multi-spacecraft missions (Cluster and MMS) in the Earth's magnetosphere and the solar wind, however, revealed electron-and ion-scale breaks in the power spectra as well as the formation of current sheet (CS) structures from ion to electron scales [20][21][22] . On the other hand, even hybrid-kinetic simulations with inertia-less electrons have already shown that in evolving turbulent CSs, the electrons become the main current carriers 15 and that these CSs thin down to the grid scale 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Spacecraft routinely observe electric-current-carrying thin plasma layers, or current sheets (CSs), in collisionless space plasmas (e.g., Nakamura et al 2006;Sundkvist et al 2007;Greco et al 2009;Podesta 2017a;Azizabadi et al 2021;Jain et al 2021;Khabarova et al 2021b). In the solar wind, CSs are formed at discontinuities that separate regions with differently directed magnetic fields (Syrovatskiǐ 1971).…”
Section: Introductionmentioning
confidence: 99%
“…These are secondary signatures identifying ion-dominated CSs. An overview of both visual and automated methods of CS identification in the heliosphere can be found in Khabarova et al (2021b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations